The Cheerleader*: a feminist mom, her pre-teen daughter†, and the spaces‡ for girls in American football§. Issue 5 (2nd September 2016) - Gullion, Jessica Smartt
Abstract: This autoethnography is a reflection of my non-linear processes of thinking with American cheerleading. A feminist professor teaching at a historical woman's university, I had stereotyped the sexism of the activity. Meanwhile, my daughter fell in love with the sport and joined a cheer squad. The main text invokes key moments critical to my thinking with cheerleading, and represents what a casual observer may have witnessed. My specific thoughts about those events are detailed in the footnotes.